Transport and Surveillance Aspects of Location-Based Services - Wigan, Marcus; Clarke, Roger (Transportation research record, 2009)
Transport is a series of movements between locations, and considerable efforts are spent to secure details of such movements for planning and modeling purposes. This paper considers the issues raised when such information is secured too well, as well as the accompanying implications for surveillance and privacy. Location is a critical aspect of both privacy and surveillance. A detailed record of locations allows all sorts of other information to be linked together, adding to information about the subject and his or her associates in the same way that a unique identifier allows dataveillance to be expanded swiftly and extensively. In this case, the information comes from allowing the linking together of both the activities and records of many people. Location technologies have far outstripped both public awareness and legal and policy attention. Addressing this gap between the public's awareness and the technological possibilities will require careful use of precise language to ensure that unexpected side effects do not occur when the problem is finally faced. This paper explores both this essential language and some of the applications and linkages that need addressing. A wider public and policy understanding of the implications of expanding capacities to track, record, and monitor location is an urgent need, because it is difficult to reverse capacities once they are integrated into a wide range of commercial, enforcement, and intelligence systems–-as is already happening.